The new general biological property of stem-like tumor cells Part I. Peculiarities of the process of the double-stranded DNA fragments internalization into stem-like tumor cells - Ritter, Genrikh S.; Dolgova, Evgeniya V.; Petrova, Daria D.; Efremov, Yaroslav R.; Proskurina, Anastasia S.; Potter, Ekaterina A.; Ruzanova, Vera S.; Kirikovich, Svetlana S.; Levites, Evgeniy V.; Taranov, Oleg S.; Ostanin, Alexandr A.; Chernykh, Elena R.; et al. (Frontiers in Genetics, 2022)
Stem-like tumor cells of ascites carcinoma Krebs-2 and Epstein-Barr virus–induced B-lymphoma were shown to possess the innate capability of binding and internalizing the TAMRA-labeled double-stranded DNA (dsDNA) probe. The process of binding and internalizing is rather complicated and composed of the following successive stages: 1) initiating electrostatic interaction and contact of a negatively charged dsDNA molecule with a positively charged molecule(s) on the surface of a stem-like tumor cell; 2) binding of the dsDNA probe to a tumor stem cell surface protein(s) via the formation of a strong chemical/molecular bond; and 3) the very internalization of dsDNA into the cell. Binding of DNA to cell surface proteins is determined by the presence of heparin/polyanion-binding sites within the protein structure, which can be competitively blocked by heparin and/or dextran sulfate, wherein heparin blocks only the binding, while dextran sulfate abrogates both binding and internalization. The abrogation of internalization by dextran sulfate implies the role of scavenger receptors in this process. Cells were shown to uptake DNA in amounts constituting ∼0.008% of the haploid genome. Inhibitors of caveolae-dependent internalization abrogate the DNA uptake in Krebs-2 cells, and inhibitors of the clathrin/caveolar mechanism block the internalization in B-lymphoma cells. In the present report, it is shown for the first time that in contrast to the majority of committed tumor cells, stem-like tumor cells of Krebs-2 and B-lymphoma carry a general positive charge on their surface.